Implications of foreign direct investment in India's retail sector - Murali Patibandla (IIMB Management Review, 2014)
Supply chain is the backbone of retail business. Adoption of an efficient supply chain between producers and consumers by modern large retailers could reduce average transaction and information costs of market exchange; generate surplus for stakeholders such as producers, farmers, and consumers; expand output; and could thereby contribute to economic growth and net employment gains. Foreign players can introduce a highly advanced supply chain and develop local producers and generate externalities. This paper develops a simple theory of supply chain and economic growth. It shows the implications of adaptation of the Wal-Mart model of retailing on India's retail business.